A Selector of Grid Resources based on the Semantic Integration of Multiple Ontologies - Silva, Alexandre P. C.; Dantas, Mario A. R. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2007: Anais do XIX International Symposium on Computer Architecture and High Performance Computing, 2007)
Different resources descriptions from different virtual organizations in a grid environment, exemplifies the challenge to match a specific resource, that could have similar characteristics, but with diverse descriptions. The use of a semantic matching method, based on ontology descriptions, is an alternative that can be considered by a software package to tackle this problem. However, recent researches indicate that fully automated systems are not able to recognize all possible relations between different ontologies. In other words, the human interaction is necessary after the recognition phase, when preliminary results are obtained from an ontology matching operation. This interaction is important in order to build a more logic knowledge to create efficient queries. In this article, we present a prototype tool which was designed and implementated to reduce issues related to match grid resource.